2016
DOI: 10.1098/rsos.160622
|View full text |Cite
|
Sign up to set email alerts
|

Endocranial volume is heritable and is associated with longevity and fitness in a wild mammal

Abstract: Research on relative brain size in mammals suggests that increases in brain size may generate benefits to survival and costs to fecundity: comparative studies of mammals have shown that interspecific differences in relative brain size are positively correlated with longevity and negatively with fecundity. However, as yet, no studies of mammals have investigated whether similar relationships exist within species, nor whether individual differences in brain size within a wild population are heritable. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Due to the difficulties of directly measuring brain size, endocranial volume is frequently used as a proxy [122–124]. In a study of red deer on the Isle of Rum, Scotland, Logan et al [119] used endocranial volume as a proxy for brain size and found positive correlations with lifespan and lifetime reproductive success. Isler et al [123] compared endocranial volume from 3813 primates, at least 89% of which were wild caught, and found it did not differ between wild and captive/tamed animals, whereas body mass varied with living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulties of directly measuring brain size, endocranial volume is frequently used as a proxy [122–124]. In a study of red deer on the Isle of Rum, Scotland, Logan et al [119] used endocranial volume as a proxy for brain size and found positive correlations with lifespan and lifetime reproductive success. Isler et al [123] compared endocranial volume from 3813 primates, at least 89% of which were wild caught, and found it did not differ between wild and captive/tamed animals, whereas body mass varied with living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, brain size does not scale linearly with body size within (Rubinstein, 1936) or across (e.g., Fitzpatrick et al, 2012;Montgomery, Capellini, Barton, & Mundy, 2010) species, brain regions do not scale uniformly with total brain size across species (see Heterogeneity in Brain Composition Within Taxonomic Groups section; e.g., Barton & Harvey, 2000;Farris & Schulmeister, 2011;Gonzalez-Voyer, Winberg, & Kolm, 2009), brain size does not uniformly scale with neuron number across taxa (see Heterogeneity in Brain Composition Within Taxonomic Groups section; Herculano-Houzel, Catania, Manger, & Kaas, 2015;Olkowicz et al, 2016), brain size does not necessarily translate into cognitive ability (see the Assumptions and Limitations About What Brains Mean for Cognition section and the Measuring Cognition Through Behavior Is Noisy Because We Use Unvalidated Proxies section), and brain size is not consistently related to variables of interest even within species (see the Does Selection Act on Brain Size? section; e.g., there are sex differences with regard to brain size and its relationship with cognition [Kotrschal et al, 2014;Kotrschal et al, 2013] and fitness and longevity [Logan, Kruuk, Stanley, Thompson, & Clutton-Brock, 2016]). Therefore, a research program that relies on one or more of these assumptions is limited in its ability to make reliable inferences about what brain size measures and what it means when such measures correlate (or not) with other traits.…”
Section: Assumptions and Limitations Of What Brain Size Measuresmentioning
confidence: 99%
“…This use of repeated measurements to separate transient fluctuations, such as measurement error variance (σ 2 em ), from the environmental variance (σ 2 E ) contrasts with the usual use of repeated measures in quantitative genetics, which is to separate the variance of stable permanent environmental effects (σ 2 P E ) from the additive genetic variance (σ 2 A )(e.g. Kruuk and Hadfield, 2007;Logan et al, 2016;Notter et al, 2017). In the first case, repeated measures are used to prevent downward bias in estimates of h 2 , in the second to prevent upward bias in σ 2 A and h 2 .…”
Section: Introductionmentioning
confidence: 99%